If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(z + 6) + -26 = 0 Reorder the terms: 4(6 + z) + -26 = 0 (6 * 4 + z * 4) + -26 = 0 (24 + 4z) + -26 = 0 Reorder the terms: 24 + -26 + 4z = 0 Combine like terms: 24 + -26 = -2 -2 + 4z = 0 Solving -2 + 4z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 4z = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 4z = 0 + 2 4z = 0 + 2 Combine like terms: 0 + 2 = 2 4z = 2 Divide each side by '4'. z = 0.5 Simplifying z = 0.5
| 4x/7x+28 | | 1-6x=19+3x | | 4x/27+8x | | 2(5z-1)-2(6-2z)=4 | | 3(2z-2)-3(5-3z)=3 | | 3y/4=0.6 | | 60-3(E-5)= | | -3x+8x^2+1=0 | | 3(r-4)=3 | | -2b=10-8.58 | | 5h+9=4h+1 | | 3L+22=9l-20 | | 6-3f=18 | | 1.4t-12=-0.6t | | 1.4t-12=4x+23 | | x^2-2bx+a^2=0 | | 500+45(5)=y | | 500+45x=y | | 0.4xsquared-40x+360=0 | | z^2+4iz+5=0 | | x+5y/x | | 3(x-7)-4(x+2)=20 | | (x+5y)/x | | 4x-1=64 | | 7/11=x/45 | | 5x+0.9= | | 7x+0.2= | | 1/3(7x-1)=1/4 | | 81=9a | | 182/7+(5*11)=9a | | 12+144+20+6/7+(5*11)=9a | | 401.28+.2x=x |